MENTORSHIP-BASED CLINIC LEARNING METHODS ON SELF EFFICACY AND CLINIC SKILLS IN COMMUNITY NURSING PROFESSIONAL PRACTICE - Yusuf, Nur Ayun R.; Jafar, Cindy Puspita Sari Haji; Wulansari, Ika (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2023)
ABSTRACTIntroduction: The learning method has a significant role in the learning process. The learning method serves as a way to deliver learning materials so that they reach students to achieve the expected competencies. One of the effective methods to improve skills and increase students' self-confidence is a mentorship program. This study aims to analyze the effect of mentorship-based clinical learning methods on students' self-efficacy and clinical skills in the practice of the community nursing profession.Methods: This study used a quasi-experimental design with a pre-test and post-test approach with a control group. The sampling technique used total sampling , for the intervention group as many as 28 students and 31 students in the control group.Results: The results showed that there was an effect of the mentorship learning method on the clinical skills of students practicing the community nursing profession ( P value = 0.000 ) where P value < 0.05 , while the self efficacy variable there is no influence of the mentorship learning method on the self-efficacy of students practicing the community nursing profession with statistical test results obtained P value = 0.454 (p > 0.05) .Conclusion: There is an effect of mentorship-based clinical learning methods on students' clinical skills, but there is no effect of mentorship-based clinical learning methods on students' self-efficacy in practicing community nursing professions. Keywords: Mentorship, clinical skills, self efficacy